Detailed chemical composition and functional properties of Ammodaucus leucotrichus Cross. & Dur. and Moringa oleifera Lamarck - Ziani, Borhane Eddine Cherif (2018)
Edible Ammodaucus leucotrichus Cross. & Dur. and Moringa oleifera Lamarck are largely used in the Algerian Sahara. In this context, soluble sugars, fatty acids, organic acids, and tocopherols were characterized. Decoctions and hydroethanolic extracts were studied regarding their phenolic compounds by HPLC-DAD-ESI/MSn, and in-vitro cytotoxic, anti-inflammatory, and antibacterial activities were evaluated. Results indicate high contents of carbohydrates (glucose and sucrose) and significant levels of protein and mineral were recorded for both plants. Malic acid was the major organic acid alongside with α-tocopherol, while PUFA was predominant in M. oleifera and MUFA in A. leucotrichus. Flavonoid derivatives were the most abundant group, being luteolin-O-(malonyl-glucoside) the main compound in A. leucotrichus and quercetin-3-O-(6″-malonyl-glucoside) and 3-O-caffeoylquininc acid the major molecules in M. oleifera. Extracts exhibited significant cytotoxicity on Hela and MCF-7 cell lines. The anti-inflammatory activity was also higher in the hydroethanolic extracts, which also revealed the highest antibacterial effects, especially for Gram-positive bacteria.